METODE GAMIFIKASI BERBASIS TRI HITA KARANA SEBAGAI ALTERNATIF PEMBELAJARAN ABAD 21 - Made Suarmini (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2019)
Gamification is the use of game metaphors, game elements and ideas in non-game contexts aimed at increasing user interaction. In the learning process, gamification can mean game elements (eg points, leaderboard, and medals) that can be used in a non-game learning context to increase student motivation and student involvement in the classroom. Using “Tri Hita Karana” as an additional element in applying gamification aims to introduce and instill existing cultural values to students. With innovations used in the learning process can help to increase students' interest and motivation in learning. Therefore, Tri Hita Karana-based Gamification is an alternative learning that can be used in the classroom.